Pengaruh Kualitas E-Service Terhadap Kepuasan Konsumen dan Dampaknya Terhadap Penjualan Online Repurchase in Lazada Indonesia di Kota Semarang - Singgih Purnomo (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2022)
This research was conducted by examining the gap between the relationship between e-service quality and customer satisfaction and its effect on repurchase intention. The study was conducted to see whether all electronic service quality variables (usage, website design, responsiveness, personalization/customization, and assurance) had an effect on total service quality and customer satisfaction which could lead to repeat purchases. The analysis technique used is SEM (structural equation modeling) with the number of respondents as many as 197 Lazada customers in the city of Semarang. The results of the goodness of fit criteria RMSEA = 0.066; NFI & NNFI = 0.96 & 0.94; IFI = 0.92; and RFI = 0.93. These results indicate that the model has a good fit and is feasible to use. Based on the results of the study, there are four hypotheses that have a positive and significant effect, namely web design, responsiveness, customization, and customer satisfaction on repurchase intentions. However, two objections were rejected, namely the ease of use and the assurance of repurchase intentions